Surgical thyroid pathology in Crimea and Sevastopol: the way COVID-19 pandemic altered the frequency and structure of diseases - O. R. Khabarov; D. V. Zima; O. F. Bezrukov; E. Yu. Zyablitskaya; E. R. Asanova; P. E. Maksimova (Исследования и практика в медицине)
Purpose of the study. To evaluate the impact of the COVID-19 pandemic on the structure of surgical thyroid pathology among the population of the Republic of Crimea and Sevastopol City in 2019–2024 through a retrospective data analysis.Patients and methods. A retrospective analysis of the data (patient medical records, electronic databases) was carried out. Patients were divided into four groups: pre-pandemic, pandemic, and post-pandemic (early and late periods). A total of 1038 cases were analyzed (684 from Crimea, 354 from Sevastopol). Only histological data from surgical specimens were included. Statistical analysis was performed using StatTech v. 4.7.1, applying Pearson’s chi-square (with Holm correction) and Cramer’s V tests. Differences were considered statistically significant at p < 0.05.Results. Analysis of 2019–2024 data revealed significant changes in the structure of surgical thyroid pathology in Crimea and Sevastopol. The post-pandemic period had an increased proportion of malignant neoplasms: thyroid cancer frequency in Crimea rose by 9.8–11.5 % (p < 0.05) and in Sevastopol by 9.8–33. 5 % (p < 0.001). Papillary carcinoma became dominant, increasing from 24.7 % to 31.0 % in Crimea and reaching 57.6 % in Sevastopol. Crimea recorded higher lymph node metastasis (up to 38.6 %,  p = 0.003) and capsular invasion (26.3 %, p < 0.001), while Sevastopol showed multicentric tumor growth during the pandemic (31.9 %, p = 0.003). A surge in toxic goiter at the pandemic peak (Crimea: 10.8 % to 26.6 %; Sevastopol: 1.6 % to 11.7 %) normalized by 2024. Gender analysis confirmed women’s predominance among patients (85–92 %), particularly in the menopausal period.Conclusion. The COVID-19 pandemic caused delayed diagnosis and increased aggressive thyroid cancer forms, linked to restricted routine care and the virus’s direct impact on thyroid tissue. The rise in aggressive thyroid cancer subtypes, including metastatic and invasive forms, reflects postponed surgeries and screening during restrictions, underscoring the need for enhanced screening programs. These findings highlight the importance of adapting healthcare systems to global crises, including reserving resources for oncology care and developing early diagnostic algorithms.